Ginsenosides Rb1 Attenuates Chronic Social Defeat Stress-Induced Depressive Behavior via Regulation of SIRT1-NLRP3/Nrf2 Pathways - Jiang, Ning; Zhang, Yiwen; Yao, Caihong; Huang, Hong; Wang, Qiong; Huang, Shuangxue; He, Qinghu; Liu, Xinmin (Frontiers in Nutrition, 2022)
Ginsenoside Rb1, a diol-type ginseng saponin, has various positive effects on the central nervous system. This study aimed to evaluate the antidepressant effects of Rb1 on chronic social defeat stress (CSDS) induced behavioral deficits and the exact neural cascades linked with inflammatory processes. The results of behavioral tests such as social interaction, tail suspension, and forced swimming revealed that oral treatment of Rb1 (35 and 70 mg/kg) alleviates depression-like behavior. Rb1 treatment increased antioxidant enzyme activity (SOD and CAT) and reduced lipid peroxidation (LPO) content in the hippocampus. Rb1 also suppressed the production of inflammatory cytokines (TNF-α, IL-18, and IL-1β) as well as microglial activation (Iba1) in response to CSDS. Moreover, Rb1 administration considerably reduced the protein expression of NLRP3 (inflammasome) and promoted the protein expressions of Nrf2, HO-1 and Sirtuin1(SIRT1) activation in the hippocampus. Our findings showed that Rb1 effectively restores the depressive-like behavior in CSDS-induced model mice, mediated in part by the normalization of oxidative stress levels. The suppression of neuroinflammation is mediated by the regulation of SIRT1-NLRP3/Nrf2 pathways. Our results asserted that the Rb1 is a novel therapeutic candidate for treating depression.